Officer's quarters at Hudson's Bay Co., Fort Colville near Kettle Falls, Washington - University of Washington Libraries. Special Collections Division. (1880)
The original building burned about 1866 and this is the later one built by Angus McDonald. Donald MacDonald, son of Angus, is one of the men seen in the picture. Caption on image: 18 Old Hudson Bay Co. post at Kettle Falls. 1833 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number Scanned from a photographic print using a Microtek Scanmaker 9600XL at 100 dpi in JPEG format at compression rate 3 and resized to 768x512 ppi. 1999.